ANASTOMOSITIS IN THE STRUCTURE OF POSTOPERATIVE COMPLICATIONS OF MINI GASTRIC BYPASS - Sattarov, O.T.; Khamdamov, B.Z.; Isomutdinov, A.Z. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Bariatric surgery is the most effective intervention to reduce obesity-related morbidity and mortality. In this regard, one of the most common and well-studied bariatric procedures is laparoscopic mini-gastric bypass. Increased insulin sensitivity detected shortly after performing such surgeries, even before significant weight loss occurs, suggests immediate systemic changes in metabolism after surgery, which are early, as even ten years after surgery, beneficial effects on glucose, lipid, and blood pressure metabolism can be seen. However, although this method of surgery is more than 25 years old, the mechanisms underlying the development of postoperative complications remain not fully understood.